2020
DOI: 10.1364/boe.378447
|View full text |Cite
|
Sign up to set email alerts
|

Additive-color multi-harmonic generation microscopy for simultaneous label-free differentiation of plaques, tangles, and neuronal axons

Abstract: Multicolor fluorescence imaging has been widely used by neuroscientists to simultaneously observe different neuropathological features of the brain. However, these optical modalities rely on exogenous labeling. Here, we demonstrate, for the first time, a label-free additive-color multi-harmonic generation microscopy to elucidate, concurrently with different hues, Alzheimer’s disease (AD) neuropathological hallmarks: amyloid β (Aβ) plaques and neurofibrillary tangles (NFT). By treating third harmonic generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The 3D imaging depth was within 250 µm limited by the objective working distance. the A similar system was recently reported in Ref [24].…”
Section: Clinical In Vivo Thg and Second Harmonic Generation Microscopementioning
confidence: 56%
“…The 3D imaging depth was within 250 µm limited by the objective working distance. the A similar system was recently reported in Ref [24].…”
Section: Clinical In Vivo Thg and Second Harmonic Generation Microscopementioning
confidence: 56%
“…The ultrashort pulse duration (38 fs) of this laser makes it ideal to generate efficient harmonic signals at the focal point. Double chirped mirrors 69 were utilized to compensate for the dispersion of the optical system for the shortest pulse width in human skin. A telescope (New port, KPX193 AR18) was used to collimate the laser light to maintain the beam size after a long traveling path.…”
Section: Methodsmentioning
confidence: 99%
“…Following Ref. 69 , the pulse group delay dispersion (GDD) at the illumination plane after the objective was − 60 fs 2 , corresponding to a pulsewidth of 28 fs. Since it has been reported that the chromatic dispersion value of water with lipid at 1300 nm is zero 70 and the group velocity dispersion value of water 71 at 1262 nm as − 47 fs 2 /mm, we thus expect that the GDD value of 300-μm-thick skin tissues at 1262 nm is on the order of − 10 fs 2 n so that its effect on lengthening the 1262 nm pulse duration is negligible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the staining image, THG could visualize more detailed brain structures, such as neuronal soma and axon fiber bundles. By taking advantage of the emission of SHG from Aβ plaques and NFTs, and THG from Aβ plaques, the same research team used a combination of SHG and THG for differential visualization of Aβ plaques and NFTs ( Chakraborty et al, 2020a ). In this additive-color multi-harmonic generation imaging, the THG-green and SHG-red pseudo-colors were used to generate the images that visualize the yellow Aβ plaques, orange-red NFTs, and green axons and dendrites.…”
Section: Optical Harmonic Generation Imaging (Ohgi)mentioning
confidence: 99%